EFFORTS TO ADDRESS THE RIGHTS OF RESTITUTION OF CHILD VICTIMS RESEARCH STUDY OF THE OFFICE OF WOMEN'S EMPOWERMENT, CHILD PROTECTION AND COMMUNITY OF BINJAI CITY - Ilmuwani Lubis; Firman Halawa; Yamirah Mandasari Saragih (PT. Radja Intercontinental Publishing, 2024)
This writing is motivated by various forms of problems which are used as complaints experienced by several communities regarding criminal acts of violence experienced by children and women. The research method used is the Empirical Juridical method with a descriptive analysis approach. The results of this research show that the efforts made by the women's empowerment, child protection and community services provide legal protection for children who are victims of domestic violence in coordination with non-governmental organizations such as the Indonesian Child Advocacy Institute (LAAI). The Indonesian Child Advocacy Institute (LAAI), physically provides child protection by means of Litigation and Non-litigation, the factors behind which a child who has experienced violence can have the right to restitution depending on the situation and conditions faced, such as victims of criminal acts of sexual violence have the right to receive restitution and recovery services in the form of compensation for loss of wealth or income, compensation for losses incurred as a result of directly related suffering as a result of criminal acts of sexual violence, reimbursement for medical or psychological treatment costs and compensation for other losses.